Effects of Pursed-Lips Breathing and Semi-Fowler Position on Oxygen Saturation in Pulmonary Tuberculosis Patients: A Quasi-Experimental Study - Fifi Ishak; Lisdayanti Usman (PT.Mantaya Idea Batara, 2026)
Pulmonary tuberculosis (TB) is an infectious disease affecting the respiratory system. Non-pharmacological interventions such as the Pursed-Lips Breathing (PLB) technique and the therapeutic Semi-Fowler position are used to improve ventilation and enhance oxygen saturation, but evidence regarding the effectiveness of these interventions remains limited. Therefore, this study aimed to analyze and compare the effectiveness of PLB, Semi-Fowler position, and their combination in improving oxygen saturation among pulmonary TB patients. This quasi-experimental study was conducted with four groups: PLB, Semi-Fowler, Combination, and Control, each consisting of 45 participants (total N = 180). Oxygen saturation levels were measured before (pretest) and after intervention (post-test). Data were analyzed using the Wilcoxon Signed Rank Test to assess pretest – post-test changes within each group and the Kruskal Wallis test to compare differences between groups. Results: Significant increases in oxygen saturation were observed in the PLB group, Semi-Fowler group, and the Combination group (p < 0.001), whereas no significant change in the Control group (p = 0.097). The greatest improvement occurred in the Combination group, with a mean post-test oxygen saturation of 96.04%, followed by the PLB group (95.62%) and the Semi-Fowler group (95.49%). There were significant differences among the four groups (p < 0.001). The highest proportion of patients achieving normal oxygen saturation was observed in the Combination group (88.9%). Conclusion: PLB, the Semi-Fowler position, and their combination therapy are effective in improving oxygen saturation among pulmonary TB patients, with the combined intervention yields the most optimal outcome